The BFG: Plays For Children - Dahl, Roald (Penguin Group, 1993)
Everybody loves the BFG. Now children can bring him to life! David Wood has created seven short plays to read and perform. With notes on simple staging, props and costumes, the plays can be produced with the minimum of experience and resources.
Keywords: Juvenile Nonfiction; Literary Criticism & Collections